On Dynamics of Certain Economic Models - Lubica Hanustiakova; Rudolf Olach (Communications - Scientific letters of the University of Zilina, 2005)
The article deals with the dynamics of two economic models. The first one is a macroeconomic model about national income and its stability. In the second model the price of a certain commodity is treated. The equilibrium points, periodic points, price cycles and their stability in the market is also observed. The article is interdisciplinary in its nature.